The calcitonin gene-related peptide family form, function and future perspectives - Hay, Deborah L.; Dickerson, Ian M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book contains a comprehensive series of reviews on the calcitonin gene-related peptide (CGRP) family of peptides. This family of peptide hormones has a diverse and constantly expanding range of important physiologic functions, including regulation of blood calcium, vascular tension, feeding behavior and pain recognition. This volume includes chapters on: The adrenomedullin peptides and signalling Ligand binding and activation of the CGRP receptor Understanding amylin receptors The CGRP-receptor component protein The calcitonin peptide family Genetic regulation of CGRP Vascular actions of CGRP and adrenomedullin Intermedin/adrenomedullin 2 function CGRP and adrenomedullin as pain-related peptides Amylinergic control of ingestive behaviour Calcitonin receptors This book discusses their receptors, physiological and pathophysiological functions and potential as clinical targets. It will appeal to researchers who study any of these peptides and those with an interest in migraine therapy due to the involvement of CGRP in this disorder. The book is unique because it brings together research on the whole peptide family for the first time in several years. It will be a useful reference volume for researchers in this area. This book will also appeal to researchers in the broader field of bioactive peptides.
Molecular and Functional Evolution of the Adrenomedullin Family in Vertebrates: What Do Fish Studies Tell Us? -- Ligand Binding and Activation of the CGRP Receptor -- Understanding Amylin Receptors -- The CGRP-Receptor Component Protein: A Regulator for CLR Signaling -- The Calcitonin Peptide Family: What Can We Learn from Receptor Knock Out and Transgenic Mice -- Gene Targeted Mouse Models of Adrenomedullin Signaling -- Genetic Regulation of CGRP and Its Actions -- Vascular Actions of CGRP and Adrenomedullin: Mechanisms and Potential Contribution to Inflammation in the Cutaneous Microvasculature -- Insights into the Function of Intermedin/Adrenomedullin 2 -- CGRP and Adrenomedullin as Pain-Related Peptides -- Amylinergic Control of Ingestive Behaviour -- CGRP Receptor Antagonists for Migraine: Challenges and Promises -- Calcitonin Receptor Expression in Embryonic, Foetal and Adult Tissues: Developmental and Pathophysiological Implications -- Conclusions and Future Perspectives.
Keywords: Medicine; Oncology; Gene expression; Endocrinology; Biomedicine; Biomedicine general; Endocrinology; Gene Expression; Cancer Research